Non-alcoholic fatty liver disease and incidence of microvascular complications of diabetes in patients with type 2 diabetes: a prospective cohort study - Deravi, Niloofar; Dehghani Firouzabadi, Fatemeh; Moosaie, Fatemeh; Asadigandomani, Hassan; Arab Bafrani, Melika; Yoosefi, Niyoosha; Poopak, Amirhossein; Dehghani Firouzabadi, Mohammad; Poudineh, Mohadeseh; Rabizadeh, Soghra; Kamel, Ibrahim; Nakhjavani, Manouchehr; et al. (Frontiers in Endocrinology, 2023)
Objective To investigate the association between non-alcoholic fatty liver disease (NAFLD) and liver enzymes with the incidence of microvascular complications (neuropathy, retinopathy, and nephropathy) in a cohort of Iranian patients with type 2 diabetes. Methods For a total population of 3123 patients with type 2 diabetes, a prospective study was designed for 1215 patients with NAFLD and 1908 gender and age-matched control patients without NAFLD. The two groups were followed for a median duration of 5 years for the incidence of microvascular complications. The association between having NAFLD, the level of liver enzymes, aspartate aminotransferase to platelet ratio index (APRI), Fibrosis-4 (FIB-4) value, and the incidence risk of diabetic retinopathy, neuropathy, and nephropathy were assessed through logistic regression analysis. Results NAFLD was found to be associated with incidence of diabetic neuropathy and nephropathy (Odds ratio: 1.338 (95% confidence interval: 1.091-1.640) and 1.333 (1.007-1.764), respectively). Alkaline-phosphatase enzyme was found to be associated with higher risks of diabetic neuropathy and nephropathy ((Risk estimate: 1.002 (95% CI: 1.001-1.003) and 1.002 (1.001-1.004), respectively)). Moreover, gamma-glutamyl transferase was associated with a higher risk of diabetic nephropathy (1.006 (1.002-1.009). Aspartate aminotransferase and alanine aminotransferase were inversely associated with the risk of diabetic retinopathy (0.989 (0.979-0.998) and 0.990 (0.983-0.996), respectively). Furthermore, ARPI_T (1), ARPI_T (2), and ARPI_T (3) were shown to be associated with NAFLD (1.440 (1.061-1.954), 1.589 (1.163-2.171), and 2.673 (1.925, 3.710), respectively). However, FIB-4 score was not significantly associated with risk of microvascular complications. Conclusion Despite the benign nature of NAFLD, patients with type 2 diabetes should be always assessed for NAFLD to ensure early diagnosis and entry into proper medical care. Regular screenings of microvascular complications of diabetes is also suggested for these patients.